Perancangan lemari aksesoris otomotif pada garasi rumah dengan sistem modular - Aesa, Galang Riezqi; Susila, Dwi Agus (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
This study aims to design an efficient and functional automotive accessory cabinet using a modular system for a home garage with limited space. Along with the growth of the global furnitur industry and the need for efficient storage space, a modular system is chosen because of its flexibility in adjusting the size of the space. This cabinet is designed to be easily disassembled according to user needs, maximizing garage space efficiency without reducing aesthetics. This study uses a qualitative method with a Design Thinking approach, involving five stages: empathize, define, ideate, prototype, and test. Teak wood is chosen as the main material because of its durability and aesthetic value. The modular design not only meets the needs of storing automotive accessories, but also supports the principle of sustainability through the use of durable and environmentally friendly materials. The results show that this modular design is effective in optimizing limited space, providing a flexible and aesthetic solution for storage in a home garage. The modular system ensures that the cabinet can be customized and used in various configurations, allowing users to optimize limited garage space. The modular system has advantages over conventional designs in optimizing limited space. Unlike traditional cabinets that have a fixed structure, the modular system allows adjustments and rearrangements as needed, making it more flexible, efficient, and can maximize every inch of space.